New endemic Fusarium species hitch-hiking with pathogenic Fusarium strains causing Panama disease in small-holder banana plots in Indonesia - Maryani, N. (Persoonia, 2019)
Fusarium species are well known for their abundance, diversity and cosmopolitan life style. Many members of the genus Fusarium are associated with plant hosts, either as plant pathogens, secondary invaders, saprotrophs, and/or endophytes. We previously studied the diversity of Fusarium species in the Fusarium oxysporum species complex (FOSC) associated with Fusarium wilt of banana in Indonesia. In that study, several Fusarium species not belonging to the FOSC were found to be associated with Fusarium wilt of banana. These Fusarium isolates belonged to three Fusarium species complexes, which included the Fusarium fujikuroi species complex (FFSC), Fusarium incarnatum-equiseti species complex (FIESC) and the Fusarium sambucinum species complex (FSSC). Using a multi-gene phylogeny that included partial fragments of the beta-tubulin (tub), calmodulin (cmdA), translation elongation factor 1-alpha (tef1), the internal transcribed spacer region of the rDNA (ITS), the large subunit of the rDNA (LSU), plus the RNA polymerase II large subunit (rpb1) and second largest subunit (rpb2) genes, we were able to identify and characterise several of these as new Fusarium species in the respective species complexes identified in this study.